’Landslide’: surprising results of the elections in India - Rothermund, Dietmar (Asien, 2004)
Indians like to talk about a 'landslide' when elections lead to an unexpected change of government as they did in May 2004. Hearing about such a dramatic event one would expect that a massive shift of the national vote produced such results. But the majority election system which India has inherited from the British often translates a shift of only a few percentages in the national vote into a major change in the number of seats won by different parties.
Elektronische Reproduktion der Druckausgabe